Rapidly growing massive abdominal sarcomatoid carcinoma on F18-FDG PET-CT scan - Tanzil Sajid; Aamna Hassan (Journal of the Pakistan Medical Association, 2023)
Sarcomatoid carcinoma is a rare type of tumour and most commonly arises in the lungs. However, rarely can it also be found in the abdomen. Sarcomatoid tumours are aggressive with large tumoural volume showing cancerous epithelial cells mixed with sarcomatous (nerve, muscle, fat etc.) features on histopathology. Most of the carcinosarcomas arise in the background of pleomorphic adenoma, originating from a myoepithelial precursor. These tumours are resistant to treatment and rapidly metastasize. We present a unique case of hepatocellular sarcomatoid sarcoma, evaluated through F18-FDG PET/CT. Keywords: Sarcomatoid sarcoma, 18F FDG PET-CT, massive abdominal mass.